A policy scan related to assisted migration as a climate change adaptation tactic in Canada reveals major policy gaps - S.J. Cooke; J. Vermey; J.J. Taylor; T. Rytwinski; W.M. Twardek; G. Auld; R. Van Bogaert; A.L. MacDonald (Canadian Science Publishing, 2024)
Assisted migration is increasingly being considered as a potential climate change adaptation tactic even though it also comes with potential risk to ecosystems and society. When implementing conservation actions that involve risk, it is prudent to have policies and guidelines to ensure that such actions are conducted in ways that conform to regional standards and consider risks. Here, we report on a policy scan focused on assisted migration in the context of climate change adaptation originally as a protected areas tactic only, but then broadened to ecosystems in Canada beyond those boundaries. Policy scans are a useful strategy for understanding the evolving policy and regulatory landscape for a given topic and can guide the development of such policies in other jurisdictions. Our scan focused on Canada, where multi-scalar governance systems exist relevant to biodiversity and environmental management. Our comprehensive policy scan (involving scans of legislation, policies, and guidelines found online and through direct inquiries with government bodies) revealed major gaps in the assisted migration policy landscape with very few provincial/territorial or federal policies in Canada. A more rudimentary scan in the United States revealed a similar pattern. There was evidence that some jurisdictions anticipated need for such policies and even a few examples of very specific policies (e.g., seeds) that had already been developed, but there were not comprehensive policies or frameworks. Governments and other relevant bodies/organizations may wish to consider working collaboratively toward the development of robust, evidence-based policies for assisted migration given that we anticipate this conservation intervention becoming more popular as climate change impacts on ecosystems become more evident and dire.